FULFILLMENT OF THE RIGHTS OF CHILDREN IN CONFLICT WITH THE LAW IN THE WOMEN AND CHILDREN SERVICE UNIT OF THE ROKAN HULU RESORT POLICE BASED ON LAW NUMBER 11 OF 2012 CONCERNING THE JUVENILE CRIMINAL JUSTICE SYSTEM - Hutabarat, santa Delima; Fahmi, Fahmi; Pardede, Rudi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACTArticle 33 paragraph (5) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, states that: